Peran Bahasa Indonesia dalam Pengaruh Aktivitas Para Pelaku UMKM di Pasar Sentral pada Pendapatan Masyarakat - Agustin, Puspita Dian; Labanu, Dini Aminarti I.; Hulinggi, Rizqy Algifahri; Yulianti, Yulianti; Gobel, Queengelina Shainayla Wala; Barokah, Siti Nur Laylatul; Nusi, Hermawati; Humalanggi, Salsabila; Sari, Meliani Puspa; Fadillah, Andi Achmad Zaqly; Makalawo, Moh. Khusnan; Taufiqurrohman, Taufiqurrohman; Wanci, Moh. Dermawan R.; Bonde, Ramanda (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The study aims to understand the role of Indonesian in fluencing the the activities of MSMEs in the Central Market on community income. The method used is descriptive qualitative, interviews with Mr. Karim Hasan, one of the traders in the Central Market, and documentation of business activities. This data is then supplemented with information from various sources discussing the role of Indonesian in influencing the activities of MSMEs. The results of the study indicate that the use of Indonesian with consumers can reduce misunderstanding in communication and transactions because Indonesia helps sellers and buyers understand information such as, the price of the goods, product quality, differences in rice type, purchase quantities. When there are no misunderstanding, the buying and selling process is smoother and more efficient, resulting in increased income Mr. Karim Hasan also said that obstacles in communication are almost never there, difficulties only arise when serving consumers who are mute. However, it can still be handled with body language, writing, or someone accompanying the consumer.